2011
DOI: 10.7124/bc.000121
|View full text |Cite
|
Sign up to set email alerts
|

Xanthine oxidase activity regulates human embryonic brain cells growth

Abstract: Aim. Involvement of Xanthine Oxidase (XO; EC1.1.3.22) in cellular proliferation and differentiation has been suggested by the numerous investigations. We have proposed that XO might have undoubtedly important role during the development, maturation as well as the death of human embryos brain cells. Methods. Human abortion material was utilized for the cultivation of brain cells (E90). XO activity was measured by the formation of uric acid in tissue. Cell death was detected by the utility of Trypan Blue dye. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Our previous results [2] indicated that the early inhibition of the XO in the human brain derived cell culture utilizing allopurinol were initiating the increase in the number of the cells in comparison with the later stage of inhibition.…”
Section: Assesment Of Xo Activity By the Estimation Of Uric Acid Formmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous results [2] indicated that the early inhibition of the XO in the human brain derived cell culture utilizing allopurinol were initiating the increase in the number of the cells in comparison with the later stage of inhibition.…”
Section: Assesment Of Xo Activity By the Estimation Of Uric Acid Formmentioning
confidence: 99%
“…Their addition into the primary cultured neurons of various brain regions from fetal rat brain significantly promoted the neuronal survival in high cell density culture (10(5) cells/cm (2), but showed no positive effects in low density cell culture (5 x 10(3) cells/cm2). This neurotrophic effect of PLP was remarkably suppressed by picrotoxin and Ifenprodil.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous experiments were proving that the low concentration of allopurinol utilized from day first to 12 increased the cells number in the cell culture. The experiments were designed for the estimation of the endogenous XO activity [4]. Our current data demonstrate that even exogenous addition of xanthine, NAD + and allopurinol does promote increase of the cells' number.…”
Section: Discussionmentioning
confidence: 61%
“…In our previous experiments, we have proved experimentally, by the inhibition of the Xanthine Oxidoreductase (EC 1.17.3.2), the one of the last and the key regulative enzymes in the chain of the purines catabolism-responsible enzymes, by its classical compound-Allopurinol, it is possible to decrease the speed of purines decay [1] [2]. In addition, we have proved, by impacting the XOR, it is possible to accelerate the cells proliferation or have an influence on the cells' deaths [2] [3] [4].…”
Section: Introductionmentioning
confidence: 99%